Recurrent Emergency Department Users: Two Categories with Different Risk Profiles - Slankamenac, Ksenija (J Clin Med, 2019)
Recurrent emergency department (ED) visits are responsible for an increasing proportion of overcrowding. Therefore, our aim was to investigate the characteristics and prevalence of recurrent ED visitors as well as to determine risk factors associated with multiple ED visits. ED patients visiting the ED of a tertiary care hospital at least four times consecutively in 2015 were enrolled. Of 33,335 primary ED visits, 1921 ED visits (5.8%) were performed by 372 ED patients who presented in the ED at least four times within the one-year period. Two different categories of recurrent ED patients were identified: repeated ED users presenting always with the same symptoms and frequent ED visitors who were suffering from different symptoms on each ED visit. Repeated ED users had more ED visits (p < 0.001) and needed more hospital admissions (p < 0.010) compared to frequent ED users. Repeated ED users visited the ED more likely due to symptoms from chronic obstructive pulmonary diseases (p < 0.001) and mental disorders (p < 0.001). In contrast, frequent ED patients showed to be at risk for multiple ED visits when being disabled (p = 0.001), had an increased Charlson co-morbidity index (p = 0.004) or suffering from rheumatic diseases (p < 0.001). A small number of recurrent ED visitors determines a relevant number of ED visits with a relevance for and impact on patient centred care and emergency services. There are two categories of recurrent ED users with different risk factors for multiple ED visits: repeated and frequent. Therefore, multi-professional follow-up care models for recurrent ED patients are needed to improve patients’ needs, quality of life as well as emergency services.